223 Healthcare Resource Utilization (HCRU) and Treatment Patterns in Men with Erectile Dysfunction (ED) and Benign Prostatic Hyperplasia-Associated Lower Urinary Tract Symptoms (BPH-LUTS) in the United States (US): A Retrospective Database Study. (1st May 2022) - Goldstein, I; Hassan, T; Zou, K; Divino, V; DeKoven, M; Imperato, J; Anupindi, VR; Li, J
ABSTRACT: Introduction: There are various treatment options for patients with ED and comorbid BPH-LUTS. Relevant clinical practice guidelines are available to help and guide physicians in making appropriate disease management decisions. However, real-world evidence comparing health-related outcomes between patients treated with tadalafil and those who did not receive any PDE5i therapy is limited. Objectives: To compare HCRU outcomes in patients with ED and BPH-LUTS treated with tadalafil or not treated with any PDE5i in the US and to compare tadalafil treatment persistence and adherence by dose. Methods: This was a retrospective real-world data study of men (aged 45+) with ED and BPH-LUTS treated with tadalafil or not treated with any PDE5i, using the IQVIA PharMetrics® Plus claims database. Outcomes included all-cause and disease-specific HCRU over the 12-month follow-up. Disease-specific was defined as claims with a diagnosis of ED or BPH-LUTS, and/or specific therapy or procedures used in the treatment of ED or BPH-LUTS. Persistence (days till discontinuation) and adherence (proportion of days covered, PDC) to tadalafil therapy was also evaluated, stratified by dose over the follow-up (10 or 20 mg as needed; 2.5 or 5 mg as once daily). Pair-wise comparisons were conducted using t-test for continuous variables and Chi-square test for categorical variables. Results: The final sample comprised 11, 351 tadalafil and 48, 722 non-PDE5i cohorts. Mean age was 57.1 and 57.9 years, respectively. All-cause HCRU : Mean number of all-cause laboratory/pathology tests (13.8 vs. 16.4) and proportion with at least one outpatient surgical visit (63.0% vs. 68.8%) or radiology exam (59.3% vs. 63.4%) were significantly lower for tadalafil cohort vs. non-PDE5i cohort (all comparisons, p<0.0001). Disease-specific HCRU : Proportion with at least one disease-specific physician office visit (55.1% vs. 91.4%), laboratory/pathology test (34.8% vs. 58.2%), radiology exam (5.8% vs. 10.8%), outpatient surgery (24.3% vs. 38.9%) or outpatient ancillary service (18.0% vs. 29.8%) were significantly lower for tadalafil cohort vs. non-PDE5i cohort (all comparisons, p<0.0001). Persistence toTadalafil : Mean persistence days (179.8 vs 61.2) and % patients without discontinuation (35.8% vs. 6.5%) were higher for daily tadalafil dose vs. as needed tadalafil dose. Adherence toTadalafil : Mean PDC [90% confidence interval] was higher for daily tadalafil dose vs. as needed tadalafil dose (0.50 [0.495, 0.508] vs. 0.20 [0.198, 0.211]). Conclusions: Patients on tadalafil used less HCRU than patients not on any PDE5i therapy. Persistence and adherence were higher in patients treated with daily tadalafil compared with as needed tadalafil therapy. The results demonstrated tadalafil's benefit in the management of men with ED and BPH-LUTS. Disclosure: Work supported by industry: yes, by Upjohn-a Pfizer division. A consultant, employee (part time or full time) or shareholder is among the authors (Viatris).